Análise do uso de indicadores sociais pelas pequenas e médias empresas da cadeia produtiva de petróleo em Macaé: um estudo de caso múltiplo - Loureiro, Walter Luiz de Mello (2013)
In the late '70s, the northern region of Rio de Janeiro state began to develop rapidly with the discovery and early exploration and production of oil and gas activities in the Campos Basin. The city of Macaé, chosen to serve as Petrobras operations base received the direct influence of this new economic order. The present study aims to investigate the main socioeconomic transformations caused by the oil industry in Macaé, assessing their impacts on local development and using some social indicators for Small and Medium Enterprises (SME s) within oil and gas supply chain of Campos Basin. The method of investigation is based on exploratory and documentary research, comparing the data in a qualitative and quantitative way, according to information available in the literature and statistical documents, and multiple case study involving five small and medium enterprises of Petro-BC Network installed in Macaé. The evaluation criteria adopted in the case study are based on the proposition of an online social indicators developed by GRI, ISE BM&FBOVESPA and IBASE, from the perspective of social dimension of Corporate Social Responsibility - CSR. The results indicate about the social and economic contradictions observed in the context of the new model of industrial development, and how to present management strategies undertaken by the enterprises interviewed concerning the Degrees of Importance and Utilization of the proposed social indicators, by intra-case and inter-case analysis. It is expected to have contributed to the understanding of the trajectory that characterizes local development in Macaé, after the arrival and deployment of the oil industry, and to the identification of criteria and practices of SMEs in the social dimension of CSR, facing the line of proposed indicators and literature review